The influence of state policy on the innovation activity of sustainable balanced economic growth in the globalization - Ortina, Hanna; Ортіна, Ганна Володимирівна; Ортина, Анна Владимировна; Leushyna, О. А. (My University, 2019)
EN: The article investigates and theoretically substantiates ways to improve the country’s investment and innovation policy, reveals negative manifestations of imperfect state policy that impede the smooth investment in the national economy. It is stated that it is impossible to create a new state innovation and investment policy of a higher level of technological development on a morally outdated production base, worn-out equipment of industrial enterprises and scientific centers. It is stated that at the present stage of development, the state administration requires not only the promotion of attracting investments from all possible sources, but also the control over their targeted use, which makes it possible to activate production and technological factors of economic development. Ways to improve the investment attractiveness are outlined and suggested. In the current conditions of dynamic economic development, fierce competition in the market between economic entities, development of science and technology, intellectualization of the main factors of production, it is necessary for enterprises to form effective mechanisms of implementation of innovation policy that will allow to achieve competitive advantages in the domestic and foreign markets. UK: У статті зроблено спробу теоретично дослідити та практично обґрунтувати шляхи вдосконалення інвестиційної та інноваційної політики країни в умовах глобалізації. Виявлено негативні наслідки неефективної державної політики, яка перешкоджає довірі до інвестиційної діяльності в національну економіку. Зазначено, що застаріла виробнича база, зношене обладнання заважає створенню нової державної інноваційно-інвестиційної політики країни. Відзначено, що сучасний етап розвитку вимагає від адміністрації не лише сприяння залученню інвестицій з усіх можливих джерел, але й контролю за їх цільовим використанням, що дає змогу активізувати виробничі та технологічні фактори економічного розвитку. Також запропоновано шляхи підвищення інвестиційної привабливості країни.
Вплив державної політики на інноваційну діяльність стійкого збалансованого зростання економіки в умовах глобалізації
Keywords: investments; innovations; public policy; competitiveness; education; scientific and technological progress; real economy; інвестиції; новації; державна політика; конкурентоспроможніст; освіта; науково- технічний прогрес; реальний сектор економіки